'What is industrial culture anyway?' Theoretical framing of the concept in economic geography. Issue 11 (2nd October 2021) - Bole, David
Abstract: In geography, industrial culture is a surprisingly understudied concept. Even when it is considered to play a role in the transformation processes of industrial cities or regions, it is not only terminologically diverse, but also lacks a firm theoretical and conceptual basis. This study conceptualises industrial culture and relates it to ongoing debates in various fields of geography by examining a range of literature from geography and related disciplines. This review structures the existing knowledge into four theoretical approaches: social class (Bourdieusian view), anthropological, institutional and evolutionary. Industrial culture is defined as a dynamic phenomenon in which past and present industrial production is embedded in the human physical environment, social structures, cognitive abilities, and institutions that may influence the future development choices of (post)industrial communities. This concept brings a more nuanced view of the less tangible aspects of culture to economic geography to strengthen its theoretical and empirical basis. This study explores how this concept can be integrated into current geographical research, focussing on the interaction between industrial culture and regional development through different approaches in economic geography (e.g., studies of regional assets, evolution of development paths, agency, deindustrialisation, innovation, entrepreneurship).